Investigation into electrochemical performance of NiO/graphene composite nanofibers synthesized by a simple method as anode materials for high-performance lithium ion batteries - Yuan, Baige; Li, Jun; Xia, Manman; Zhang, Ying; Lei, Ruyan; Zhao, Peng; Li, Xiao (Materials research express, 2020)
The NiO/graphene (NiO/G) composite nanofibers were successfully synthesized by simple electrospinning followed by heat treatment. They as anode materials for lithium ion batteries demonstrated the more outstanding electrochemical performance when compared with the NiO + Ni composite nanofibers as the reference. NiO/G exhibited a higher discharging/charging capacity (about 712 mAh g−1 at the third cycle) with a coulombic efficiency of nearly 100% than NiO + Ni (547 mAh g−1). NiO/G also demonstrated the excellent cycling stability due to its higher discharging capacity of 571 mAh g−1 and retention rate of 78% than NiO + Ni (184 mAh g−1 and 33%) when subject to 50 cycles at 100 mA g−1. Moreover, its rate performance was also greatly improved when compared with NiO + Ni owing to its higher discharging capacity (305 mAh g−1, 556 mAh g−1) and retention rate (44%, 80%) at the current density increased from 100 mA g−1 to 2000 mA g−1, and then recovered to 100 mA g−1. The outstanding electrochemical performance of the NiO/G electrode is closely related to its lower ohmic resistance (2.1 )/charge transfer resistance (86.5 ), and stronger diffusion capability of Li+ resulting from the high specific surface area, excellent conductivity and a certain charge storage capacity of graphene.